PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BANK MANDIRI TBK KOTA BEKASI - Berto Armando Aliando; Irawan Noor (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of simultaneous and partial competence and motivation on employee performance at PT. Bank Mandiri Tbk Bekasi City. The method used is quantitative method using regression analysis. The results of the study reveal that there is a partial or simultaneous influence of competence and motivation on employee performance.